O problemu kazenske odgovornosti - Ambrož, Matjaž (Pravnik, 2024)
The author briefly presents an article by Professor Ljubo Bavcon on the problem of criminal responsibility, originally published in 1959 in the Revija za kriminalistiko in kriminologijo (Journal of Criminalistics and Criminology). It offers a comprehensive report from an international symposium in Strasbourg, enriched with Bavcon’s scientific credo regarding the issues discussed. The core of the discussed problem was the clash between two views on criminal responsibility. The old view, also known as "classical criminal law", was based on a metaphysical notion of freedom, wherein a criminal offence was perceived as the outcome of an individual’s free, albeit malevolent, will . The response to this was punishment, intended both as a deterrent and as a form of penance - a means to frighten and reform the perpetrator’s evil will. As a counterpoint to this classical view, positivist views emerged, viewing the individual as a product of heredity and environmental factors, thus a deterministic entity. By denying free will, these perspectives also deny the concept of culpability - yet they acknowledge the necessity for society to defend itself against crimes and their perpetrators. This defence of society against criminality is no longer perceived as "deserved punishment" but rather involves various forms of treatment of criminals and their removal from the environment. Bavcon’s perspectives represent a compromise, somewhere between the heritage of the classical school and the new impulses brought by the New Social Defence Movement. Although the ideas of abolishing the concepts of guilt and deserved punishment fell silent in later developments of criminal law, recently there has been a new rise of ideas to expel moralistic undertones from criminal law, and to reorganise the operation of the criminal justice system according to the principles of public health systems. This suggests that the evolution of criminal law occurs in cyclical phases.
Keywords: criminal law; criminal responsibility; criminality; guilt; kazen; kazenska odgovornost; kazensko pravo; kaznovalno pravo; kriminaliteta; krivda; penal law; punishment